Distinguishing between acute and subacute massive pulmonary embolism by conventional and Doppler echocardiography. Issue 4 (October 1993) - Kasper, W; Geibel, A; Tiede, N; Bassenge, D; Kauder, E; Konstantinides, S; Meinertz, T; Just, H
Abstract : OBJECTIVE–To determine the ability of conventional and Doppler echocardiography to distinguish between minor, acute massive, and subacute massive pulmonary embolism in patients with confirmed pulmonary embolism. DESIGN–Prospective study of a consecutive series of 47 patients with confirmed pulmonary embolism. SETTING–Department of internal medicine, university clinic. PATIENTS–11 patients (23%) had minor, 23 patients (49%) had acute massive, and 13 patients (28%) had subacute massive pulmonary embolism. RESULTS–Dilatation of the right ventricular cavity (33 (92%)) and asynergy of the right ventricular free wall (29 (81%)) were seen only in patients with acute and subacute massive pulmonary embolism (n = 36). 23 (64%) with pulmonary hypertension had tricuspid regurgitation. The velocity of the tricuspid regurgitant jet correlated with the pulmonary arterial pressure (r = 0.88, SEE = 11.6 mm Hg) and was significantly lower in patients with acute massive pulmonary embolism (3.0 (0.4) m/s, n = 12) than in patients with subacute massive pulmonary embolism (4.2 (0.6) m/s; n = 11) (p < 0.001). The use of predefined indices (right ventricular free wall thickness > 5 mm; tricuspid regurgitant jet velocity > 3.7 m/s; and the occurrence of both a dilated right ventricular cavity with normal interventricular septal motion, or an inspiratory collapse of the inferior vena cava, or both) correctly identified 11 of 13 patients (85%) with subacute massive pulmonary embolism. CONCLUSION–Conventional and Doppler echocardiography were successful in evaluating the haemodynamic consequences of pulmonary embolism.